Pengaruh Celebrity Endorser dan Electronic Word of Mouth terhadap Minat Beli dengan Brand Image sebagai Variabel Mediasi pada E-Commerce Tokopedia - Devie Rusiana; Sri Setyo Iriani; Andre Dwijanto Witjaksono (Jurnal Maksipreneur, 2023)
The era of technology, business competition, and increasingly rapid business growth requires companies to have an efficient and effective marketing strategy. One of the marketing strategies that can generate buying interest is celebrity endorsers and electronic word of mouth (E-WOM). The purpose of this research is to find out how much influence the celebrity endorser and E-WOM variables have on buying interest with the brand image as a mediating variable in Tokopedia e-commerce. This research is of the type of explanatory research with research subjects, namely all consumers who know Tokopedia e-commerce. Determination of the research sample using purposive sampling method with a total of 120 respondents. The processing of this research data uses Partial Least Square (PLS) analysis as a data analysis technique, namely SmartPLS as a tool for processing data. The results of this study indicate that celebrity endorsers have a positive and significant influence on purchase intention, while E-WOM does not have a significant influence on the purchase intention of Tokopedia consumers. Furthermore, celebrity endorsers, E-WOM, and brand image have a positive and significant influence on the buying interest of Tokopedia consumers. Based on the mediation test, the results of this study found that Tokopedia's brand image was able to mediate the influence of celebrity endorsers and E-WOM on consumer buying interest.